Strengthening Academic Integrity among Generation Z in the Age of Artificial Intelligence: An Islamic Academic Ethics Perspective - Elliyatul Munawwarah; Syarifuddin (Yayasan Azhar Amanaa Yogyakarta, 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed higher education by providing Generation Z students with greater access to information, personalized learning, and enhanced academic productivity. However, the widespread adoption of generative AI has also introduced new ethical challenges, including plagiarism, excessive dependence on AI-generated content, diminished critical thinking, and declining academic responsibility. This study aims to examine the role of Islamic academic ethics in strengthening academic integrity among Generation Z in the era of Artificial Intelligence. Employing a qualitative approach through a narrative literature review, the study synthesizes contemporary literature on AI, academic integrity, and Islamic ethics published between 2023 and 2025. The findings indicate that existing approaches to AI governance primarily emphasize technical and regulatory principles, such as transparency, accountability, and fairness, while paying limited attention to the moral and spiritual dimensions of technology use. From an Islamic perspective, academic integrity extends beyond compliance with institutional regulations and is grounded in ethical values such as ṣidq (honesty), amānah (trustworthiness), 'adl (justice), mas'ūliyyah (responsibility), and maṣlaḥah (public welfare). These values provide a normative framework that guides the responsible use of AI without undermining intellectual originality or scholarly accountability. This study proposes a conceptual framework that integrates AI literacy, institutional governance, and Islamic academic ethics to promote responsible AI use in higher education. The study concludes that AI should function as a learning partner rather than a substitute for human reasoning, and that integrating Islamic academic ethics into higher education policies and practices can strengthen academic integrity while supporting ethical and sustainable digital transformation.